Isotope labeling in Biomolecular NMR - Atreya, Hanudatta S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
One of the major advancements in NMR spectroscopy of biomolecules has been the development of methods for isotope labeling. At the same time there has been a rapid progress in the number of NMR experiments that utilize such isotope labeled samples. Thus a combination of isotopic labeling and multidimensional, multinuclear experiments has significantly expanded the range of problems in structural biology amenable to NMR. This book is intended to serve as a compendium of isotope labeling for the biomolecular NMR community providing comprehensive coverage of the existing methods and latest developments along with protocols and practical hints on the various experimental aspects. Researchers in academia or industry will find it useful to have a single book covering a wide range of topics including the emerging areas of large/membrane proteins, RNA, metabolonomics and solid state NMR.
Keywords: Medicine; Spectroscopy; Biotechnology; Life sciences; Cytology -- Research_xMethodology.; Biomedicine; Biomedicine general; Spectroscopy/Spectrometry.; Biotechnology; Biological Techniques; Life Sciences, general; Biological Techniques